Pengukuran Kualitas Website Skill Academy Terhadap Kepuasan Pengguna Menggunakan Metode Webqual 4.0 - Izmi Habiba; Ganda Wijaya (Paradigma - Jurnal Komputer dan Informatika, 2022)
Development service or self-training currently has transformed along with the development of digital technology. Skill Academy becomes a solution in the community to develop technical and soft skills without constraints such as the limitation of time, place, and energy. However, the Skill Academy website sometimes still experiences errors, such as material or tutorial videos cannot be played and certificates not being printed according to the schedule. Therefore, this study aims to find out how the quality of the Skill Academy website on the user satisfaction using the Webqual 4.0 method. Webqual 4.0 method has three instruments, Usability, Information Quality, and Service Interaction Quality. The primary data was obtained by disseminating a questionnaire containing 22 questions about website quality and 5 questions about user satisfaction. The data were obtained using a non-probability sampling technique, which was purposive, with 100 respondents. The data analysis method used was multiple linear regression using SPSS 25 tools. The results of the study showed that the three Webqual 4.0 instruments simultaneously had an impact on user satisfaction or 58.1%, while the rest was defined by other factors outside this research model. The results for the influence of each instrument were found that Usability did not have significant influence, while Information Quality and Service Interaction Quality had a significant influence on User Satisfaction.